5+6*8+h=7*3+h

Simple and best practice solution for 5+6*8+h=7*3+h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6*8+h=7*3+h equation:


Simplifying
5 + 6 * 8 + h = 7 * 3 + h

Multiply 6 * 8
5 + 48 + h = 7 * 3 + h

Combine like terms: 5 + 48 = 53
53 + h = 7 * 3 + h

Multiply 7 * 3
53 + h = 21 + h

Add '-1h' to each side of the equation.
53 + h + -1h = 21 + h + -1h

Combine like terms: h + -1h = 0
53 + 0 = 21 + h + -1h
53 = 21 + h + -1h

Combine like terms: h + -1h = 0
53 = 21 + 0
53 = 21

Solving
53 = 21

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 23-3m=5m+7 | | (2y^2+x)(y^2-7x)= | | (-1+6i)(3-5i)= | | 8[d+5]=12d-8 | | 3x-9=3(5-3x) | | 70-40+10x=12x+40-40 | | 3(x-3)-2(x+1)= | | 96t-16t^2-80=0 | | 5x+5=-115 | | 4+5x+9=7x-1 | | 4x^2-7x+11=9x+4 | | 0.75m+3=9 | | 2x-4(3-x)=7x+5 | | 5a-(2-a)=2a-14 | | 32t+-12=3t+42 | | 4[a+3]=2a+62 | | 24513465134+134613461= | | 19+t=-133 | | -14=w+3 | | 7z+14=5z+29 | | 18n=13 | | H=90-5t^2 | | 12=-4t | | 4+5x+9=7x+1 | | 8x+2=-6+3x+23 | | x^4+2x^2-36=0 | | (4x+5y)+(x+7y)= | | 1.5-0.04x=1.5 | | (x^2)-(2x)+(2)=0 | | 8+2=-6+3x+23 | | 5x+11y=-13 | | 7(v+3)-4v=27 |

Equations solver categories